Investigation of antileshmanial activities of Cuminum cyminum based green silver nanoparticles on L. tropica promastigotes and amastigotes in vitro - Bagirova, Melahat; Dinparvar, Sahar; Allahverdiyev, Adil M.; Unal, Kubra; Abamor, Emrah Sefik; Novruzova, Metanet (ELSEVIER, 2020)
Leishmaniasis is one of the most important parasitic diseases, which is caused by Leishmania species. Nowadays; although pentavalent antimonials are used as the basic treatment option for Cutaneous Leishmaniasis, high cost, toxicity and resistance of the parasites to the medication over time are some important limitations causing several problems in the treatment. In recent years, the progress in the field of green nanotechnology provides the development of green nanoparticle-based treatment methods for Cutaneous Leishmaniasis. The importance of green nanoparticles has gradually increased due to their special reductive, stabilizing, antioxidant and non-toxic properties. Although there are many studies based on green nanoparticles against Leishmania parasites, we have not found any research about antileishmanial activities of biosynthesized silver nanoparticles (Bio-AgNPs) using Cuminum cyminum L (Cumin) seed extract. Therefore for the first time in this study in vitro antileishmanial effects of Bio-AgNPs prepared from Cumin seed extract were examined on L. tropica promastigote and amastigote forms and their efficacies were compared with chemically synthesized AgNPs. During the experiments, antileishmanial effects of synthesized nanoparticles were determined on both promastigote and amastigote forms of Leishmania parasites by detecting different parameters such as proliferation, infection index and produced nitric oxide (NO) amounts from macrophages. According to the results, it was shown that Bio-AgNPs and AgNPs excessively inhibited L. tropica promastigotes and amastigotes by significantly decreasing proliferation rates of promastigotes and metabolic activities of amastigotes, as well. Moreover, infection index rates of macrophages revealed remarkable anti-amastigote performances of Bio-AgNPs. Besides, Bio-AgNPs stimulated macrophages to release NO to kill Leishmania parasites. Consequently, for the first time, Bio-AgNPs were found to be more effective on both forms of Leishmania parasites than AgNPs. Obtained results indicated high antileishmanial potential of green nanoparticles on L. tropica parasites, causative agents of Cutaneous Leishmaniasis. Thus, obtained results demonstrated that green nanoparticles can lead to the development of new, safer, stable and more effective antileishmanial formulations against Cutaneous Leishmaniasis.
Keywords: L. tropica; Green nanotechnology; Metallic nanoparticles; Treatment; MEDIATED SYNTHESIS; AMPHOTERICIN-B; LEAF EXTRACT; Parasitology; Tropical Medicine